High-intese exercise and testosterone suplementation in individuals with heart failure Exercício intenso e suplementação de testosterona em portadores de insuficiência cardíaca - de Mara L.S.* (2014)
Introduction: Heart failure is a syndrome related to neuroendocrine alterations and limitations on daily activities associated with poor quality of life. Little is known about the effects of high-intensity exercise and testosterone supplementation therapy (TST) on heart failure patients with hypotestosteronemia. Objective: To evaluate the effects of high-intensity exercise and testosterone supplementation on quality of life and aerobic power in these patients. Methods: Nineteen heart failure patients (age=58 ± 10 years; ejection fraction= 34 ± 8%) were randomized to either a high-intensity exercise group (control; n=9) or high-intensity exercise group with hormonal supplementation (intervention; n=10). Patients exercised (40 minutes, 90% peak oxygen consumption) for 12 weeks, three times weekly and intervention group received testosterone in the first and sixth weeks. Functional capacity measurements and Minnesota Living With Heart Failure Questionnaire (MLWHFQ) scores were obtained before and after the study period. Results: Within control and intervention group respectively there was an increase in peak oxygen uptake (12% vs. 15%; p<0.05 and p<0.01), in six-minute walk test distance (15% vs. 29%; p<0.05 and p<0.01), decrease in global MLWHF score (54.1% vs. 54.%; p<0.01 and p<0.05); in physical component (52% vs. 54%; p<0.01 and p<0.05); in emotional component (60%; within intervention group; p<0.05), and in remaining components (59%; within control group; p<0.01). No differences between groups were observed after treatment. There was no significant correlation between MLWHFQ score and peak uptake oxygen changes (r=0.01; p=0.981; within control group and r= 0.46; p=0.178; within intervention group). Conclusion: High-intensity exercise improves functional capacity and quality of life scores after 12 weeks of treatment.